2016
DOI: 10.2135/cropsci2016.03.0151
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Marker Information in the Analysis of Multi‐Environment Trials Helps Differentiate Superior Genotypes from Promising Parents

Abstract: P lant breeding programs aim to develop new crop varieties with improved characteristics over existing ones available to farmers. Appropriate methods of selection are crucial to successfully identify the best possible parents for crossing, and to choose the best performing genotypes to progress in the program. Both objectives generally involve evaluating the genotypes under consideration in series of designed experiments across several locations and years.Multi-environment trials (MET) are series of field expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The data collected were first subjected to a linear mixed model by residual maximum likelihood (REML) procedure (Patterson and Thompson 1971) to estimate the variance parameters and the empirical Best Linear Unbiased Predictions (E-BLUPs) for random effects using ASReml-R 4 (Butler et al 2018). The univariate Genomic-BLUP model, including the random interaction term between the genomic effect of the i th clone and the j th site, is represented by the model described in Borgognone et al (2016) and Smith and Cullis (2018), which is as follows:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data collected were first subjected to a linear mixed model by residual maximum likelihood (REML) procedure (Patterson and Thompson 1971) to estimate the variance parameters and the empirical Best Linear Unbiased Predictions (E-BLUPs) for random effects using ASReml-R 4 (Butler et al 2018). The univariate Genomic-BLUP model, including the random interaction term between the genomic effect of the i th clone and the j th site, is represented by the model described in Borgognone et al (2016) and Smith and Cullis (2018), which is as follows:…”
Section: Discussionmentioning
confidence: 99%
“…The vectors of random effects u p , u g and e are assumed pairwise independent with Gaussian distribution, with a mean of zero. The variance matrices for u p , u g and e were as described in Borgognone et al (2016) and Smith and Cullis (2018). The random genotype effect (u g Þ in the model comprised the clone effects nested within sites and hence referred to as clone by site effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burgueno et al (2012) state that MET models can boost predictive power in acrossenvironment prediction and also showed that modeling G×E using information on molecular markers and/or pedigree gives better prediction accuracy than not using molecular markers and pedigree information. Borgognone et al (2016) and Tolhurst et al (2019) recently discussed fitting MET models that incorporated genomic additive relationship matrices. They discuss the superiority of these models over their pedigree counterparts.…”
Section: Genotype By Environmentmentioning
confidence: 99%
“…Smith and Cullis (2018) also present a factor analytic selection tool (FAST) which examines measures of overall performance and stability across environments. The FAST method is applicable to MET analyses where the first order FA loadings are positive and represent the majority of the explained variation.Authors such asOakey et al (2016),Borgognone et al (2016) andTolhurst et al (2019) discuss using marker based additive relationship matrices in a mixed model MET analysis incorporating spatial effects and factor analytic variance structures for both the additive effects and residual genetic effects.…”
mentioning
confidence: 99%